Analisis Manajemen Rantai Pasok (Supply Chain Management) Guna Optimalisasi Distribusi Usaha Mikro Kecil Menengah Pengepulan Kepiting di Wilayah Tarakan - Hidayat, Nurul; Asmanita Wati, Nur Zulkadaria; Oktaviani, Neli (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Supply chain management (SCM) is a strategy that refers to the internal activities of an organization and the number of businesses in the supply chain to support the long-term performance of the system and the entire supply chain. A lot of supply chain management is implemented, such as incorporating suppliers as colleagues in the raw material supply phase, building good relationships with customers for consumer enjoyment, and providing information to suppliers about product improvements. customers and competitive tactics for competitive advantage to measure performance levels to gain confidence in the quality of goods appropriate for the market. Therefore, in the crab collecting supply chain distribution model, it is best for supply chain members to agree on time, quantity and quality, so that the flow of products, finances and information is more organized. Crab collecting supply chain model where farmers distribute crabs to crab collectors, then crab collectors deliver crabs to retailers in traditional markets, then final consumers who enter the market then buy crabs directly from retailers. This research was conducted at Bering I Harbor, Selumit Pantai, Central Tarakan, Tarakan City, North Kalimantan at Pak Anwar's crab collection, the results will be analyzed through observation and interviews, so that information can be obtained whether the application of Supply Chain Management applied to the crab collection distribution system is optimal. or not yet.